Technological Trends in CFD Applications - Islabão de Islabão,Genizia (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2010)
This article discusses a survey on the technology of Computational Fluid Dynamics (CFD) in various areas of knowledge and applied particularly in polymers, with scientific articles and patents as sources of information. All the data were mined using computational, fluid and dynamic as keywords. It was observed that private companies are responsible for regulatory filings and universities, research centers and institutes hold patents related to CFD. Moreover, most of the papers selected have authors affiliated with universities and research institutes. From the found papers, 25% are related to polymers, surpassing the percentage of 10% found in the analysis of patents.